Dithiobiurets as Corrosion Inhibitors for Copper in 3.5% NaCl Solution - Yadav,M. (2010)
The inhibition of copper corrosion in 3.5% NaCl solution has been studied at 25 ºC using three inhibitors: 1-phenyl-2,4-dithiobiuret(Inh I), 1-p-methoxyphenyl-2,4-dithiobiuret(Inh II) and 1-p-chlorophenyl-2,4-dithiobiuret(Inh III). The inhibition efficiencies of these compounds have been evaluated by weight loss and electrochemical methods (impedance spectroscopy and polarisation curves). The surface study was done by using SEM and ESCA techniques. The inhibition efficiencies of the inhibitors follow the sequence Inh II > Inh I > Inh III. The inhibitors Inh I, Inh II and Inh III appear to inhibit corrosion process through the formation of a protective film which was found to consist of Cu(I)-inhibitor complex, cuprous chloride CuCl or CuCl2- complex ions or both on the surface.